1995
DOI: 10.1093/oxfordjournals.aje.a117616
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Compliance with Annual Screening for Fecal Occult Blood

Abstract: In a randomized, controlled trial of fecal occult blood screening for colorectal cancer, the Minnesota Colon Cancer Control Study carried out 11 annual mail screens in two phases between 1976 and 1992. This long-term compliance record of 15,476 individuals is summarized and related to demographic characteristics as well as to the screening experience of the participants. There was a strong and consistent effect of age, with peak compliance among participants about 70 years old, and lower compliance among the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…Results from this study show that, relative to ReParticipants, Dropouts were more likely to be 70-74 years of age, the oldest age band offered screening, consistent with previous findings (Thomas et al, 1995). Examination of Late Entrants revealed that invitees in the oldest age band are least likely to take up a second round invitation if they did not previously participate.…”
Section: Discussionsupporting
confidence: 88%
“…Results from this study show that, relative to ReParticipants, Dropouts were more likely to be 70-74 years of age, the oldest age band offered screening, consistent with previous findings (Thomas et al, 1995). Examination of Late Entrants revealed that invitees in the oldest age band are least likely to take up a second round invitation if they did not previously participate.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in agreement with a further analysis which used a lagged dependent variable of uptake one period before as predictor variable and analysed these six different health check-ups 46. Different other studies have confirmed the importance of past screening behaviour for recent uptake of screening examinations such as for mammographies,59 smear tests60 and faecal occult blood test,61 and also a systematic review confirmed that past screening examinations had a positive influence on a recent screening examination 26. Persistence in screening behaviour, control follow-ups to check unclear test results from the previous health check-up and shorter recommended time intervals for some of the analysed health check-up (blood pressure check, cholesterol test, dental screening and eyesight test) are of importance to explain the significance of the 1-year lagged dependent variable as predictor variable.…”
Section: Discussionsupporting
confidence: 87%
“…Actual (transitory) household income had no effect on any of the analysed health check-ups and averaged (permanent) household income had a significant influence only on the uptake for dental screening and eyesight tests. No effect of actual household income on attendance rates has also been found for other screening examinations such as breast cancer screening,82 cervical cancer screening73 and colorectal cancer screening 61. This result is important in comparison with the other analysed free health check-ups, because income effects exist for access to preventative health services for which a charge has to be paid in comparison with preventative services for which no charge exists.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Th omas et al ( 23 ) evaluated longitudinal adherence with annual FOBT screening in the Minnesota Colon Cancer Control Study. Th ey found that 74 % of subjects were compliant with FOBT testing over the 5-year study period, although their analysis was based on population-level data and not individual subjects.…”
Section: Discussionmentioning
confidence: 99%